1966
DOI: 10.1128/jb.91.5.1736-1743.1966
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Morphogenesis, and Virulence of Candida albicans after Oral Inoculation in the Germ-Free and Conventional Chick

Abstract: , N.Y.), AND A. W. PHILLIPS. Growth, morphogenesis, and virulence of Candida albicans after oral inoculation in the germ-free and conventional chick. J. Bacteriol. 91:1736-1743. 1966.-The effects of intestinal bacteria on the multiplication, morphogenesis, and infectivity of Candida albicans in the alimentary tract were investigated by comparing results obtained in germ-free and conventional chicks after oral inoculation. This challenge resulted in the establishment of large numbers of the pathogen in the alim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1970
1970
1991
1991

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…In previous studies, C. albicans has been administered to germ-free mice and chickens. Balish and Phillips (2) have shown that oral challenge with C. albicans resulted in crop infections in all germ-free chicks, whereas conventional chicks were not infected. They concluded that the enteric microbial flora of the conventional chick provides protection against candidiasis.…”
mentioning
confidence: 99%
“…In previous studies, C. albicans has been administered to germ-free mice and chickens. Balish and Phillips (2) have shown that oral challenge with C. albicans resulted in crop infections in all germ-free chicks, whereas conventional chicks were not infected. They concluded that the enteric microbial flora of the conventional chick provides protection against candidiasis.…”
mentioning
confidence: 99%
“…Under natural conditions, neonates acquire C. albicans from their mothers early in life, and the yeast usually persists as a minor and innocuous component of the mucosal flora thereafter. Apparently, the normal bacterial flora inhibits the growth of C. albicans in the alimentary tract since oral therapy with antibacterial antibiotics often results in dramatic increases in the number of viable C. albicans on mucosal surfaces (1,7,10,32).…”
mentioning
confidence: 99%
“…Because the oral cavity and GI tract are common sites of colonization in humans and recognized portals of entry for Candida (3, 7, 14-16), models in which the GI tract is employed as the route of fungal challenge have been developed (1,11,12,17,18). Since these organisms are ordinarily commensal and are opportunistic only when the host defenses are altered, our model host was given antibiotics and cytoreductive agents at doses and in a pattern that would simulate the setting in our human patient population.…”
mentioning
confidence: 99%